(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The article is of theoretical – empirical nature, its purpose is to diagnose and evaluate competitive conditions in the sector using the Porter’s "5 forces model. The paper presents Porter’s model as an analytical tool, that can be used by manufacturers to support competitive analysis, which is a prerequisite for making optimum decisions in a dynamic market environment. In the light of research has been assessed, that the level of attractiveness in the analyzed sector is average, the level of competition, high. The competitiveness analysis was carried out ex post based on the data of the years 2007-2012 concerning the market activity of the main competitors in the field of concrete building and road materials operating in the Central Pomerania region. The company internal documentation, interviews with company executives and websites and as industry magazines as well, were the main sources of information. The literature on strategic analysis of the company in the theoretical part of the article was helpful.